2021
DOI: 10.3847/1538-4357/ac12c8
|View full text |Cite
|
Sign up to set email alerts
|

Lower-luminosity Obscured AGN Host Galaxies Are Not Predominantly in Major-merging Systems at Cosmic Noon

Abstract: For over 60 years, the scientific community has studied actively growing central super-massive black holes (active galactic nuclei -AGN) but fundamental questions on their genesis remain unanswered. Numerical simulations and theoretical arguments show that black hole growth occurs during short-lived periods (∼ 10 7 -10 8 yr) of powerful accretion. Major mergers are commonly invoked as the most likely dissipative process to trigger the rapid fueling of AGN. If the AGN-merger paradigm is true, we expect galaxy m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…AGN feedback can take the role of self-limiting SMBH growth through the ejection or heating of gas by radiatively coupled outflows or jets (e.g., Nesvadba et al 2010;Couto & Storchi-Bergmann 2023), or positive feedback where SMBH growth is coupled to host star formation by compressing the ISM (e.g., Silk 2013). Perhaps the most striking example of AGN feedback is heating of the intracluster medium by largescale radio jets hosted by massive cD galaxies (see, e.g., the famous example of the Perseus cluster; Fabian et al 2003Fabian et al , 2006 Several previous studies have found strong evidence for an enhanced incidence of major galaxy mergers among samples of radio-loud AGN (Heckman et al 1986;Colina & de Juan 1995;Ivison et al 2012;Ramos Almeida et al 2012;Chiaberge et al 2015;Kaviraj et al 2015;Noirot et al 2018), and in contrast to the less conclusive results for AGN samples selected by other criteria (e.g., Grogin et al 2005;Gabor et al 2009;Georgakakis et al 2009;Rosario et al 2015;Lambrides et al 2021;Sharma et al 2024). Understanding why galaxy mergers seem to be ubiquitous among radio-loud AGN, and not among other AGN samples, may help give us better insight into the dynamical (co)evolution between SMBHs, AGN, and their host galaxies.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…AGN feedback can take the role of self-limiting SMBH growth through the ejection or heating of gas by radiatively coupled outflows or jets (e.g., Nesvadba et al 2010;Couto & Storchi-Bergmann 2023), or positive feedback where SMBH growth is coupled to host star formation by compressing the ISM (e.g., Silk 2013). Perhaps the most striking example of AGN feedback is heating of the intracluster medium by largescale radio jets hosted by massive cD galaxies (see, e.g., the famous example of the Perseus cluster; Fabian et al 2003Fabian et al , 2006 Several previous studies have found strong evidence for an enhanced incidence of major galaxy mergers among samples of radio-loud AGN (Heckman et al 1986;Colina & de Juan 1995;Ivison et al 2012;Ramos Almeida et al 2012;Chiaberge et al 2015;Kaviraj et al 2015;Noirot et al 2018), and in contrast to the less conclusive results for AGN samples selected by other criteria (e.g., Grogin et al 2005;Gabor et al 2009;Georgakakis et al 2009;Rosario et al 2015;Lambrides et al 2021;Sharma et al 2024). Understanding why galaxy mergers seem to be ubiquitous among radio-loud AGN, and not among other AGN samples, may help give us better insight into the dynamical (co)evolution between SMBHs, AGN, and their host galaxies.…”
Section: Introductionmentioning
confidence: 98%
“…galaxy mergers might be the dominant AGN-triggering mechanism (especially at high AGN luminosities) through galaxy-wide, gravitationally induced torques which drive gas toward the galactic center (as bolstered by various semianalytic and numerical works, e.g., Hopkins et al 2006). Curiously, there has been a substantial number of studies which both seem to support (e.g., Koss et al 2010;Ellison et al 2011;Hong et al 2015;Weston et al 2017;Goulding et al 2018;Gao et al 2020) and oppose (e.g., Cisternas et al 2011;Kocevski et al 2012;Karouzos et al 2014;Villforth et al 2019;Lambrides et al 2021) the relevance of major galaxy mergers in triggering AGN. Collectively, these conflicting results suggest that the physical properties of both AGN and their host galaxies, and extragalactic environments, may be pertinent when considering the role of galaxy mergers toward their initial triggering (or even sustained fueling).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies are in conflict with one another over the role mergers play in triggering an AGN. While many have found either an increased AGN fraction in merging systems (Ellison et al 2011;Satyapal et al 2014;Donley et al 2018;Goulding et al 2018) or an increased merger fraction in AGN hosts (Chiaberge et al 2015;Fan et al 2016;Gao et al 2020;Marian et al 2020;Breiding et al 2024), others have found no such connection between AGNs and mergers (Grogin et al 2005;Cisternas et al 2011;Böhm et al 2013;Villforth et al 2017;Marian et al 2019;Lambrides et al 2021). Selection biases almost certainly contribute to this dissonance.…”
Section: Introductionmentioning
confidence: 99%
“…For a recent review of obscured AGN see Hickox and Alexander [14]. By contrast to the merger-driven model, secular AGN triggering, through dynamical processes internal to the host galaxy, dominates among lower luminosity, but much more numerically common, AGN [13,15,16].…”
Section: Introductionmentioning
confidence: 99%